PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK UNTUK MENINGKATKAN KREATIVITAS SISWA MTs ROUDLOTUR ROSMANI KOTA BENGKULU - Rio Putra, Deko; Dora, Renita; Martina, Lidian; Bella, Sinta (Jurnal Ilmu Pendidikan Islam, 2025)
This research aims to explore the application of the Project-Based Learning (PjBL) model in increasing student creativity at MTs Roudlotur Rosmani, Bengkulu City. The PjBL model provides opportunities for students to learn through hands-on experience in real, relevant projects, which can encourage critical thinking, collaboration and innovation skills. This research used the classroom action research (PTK) method which was carried out in two cycles with the research subjects being class VIII students. The research results show that the application of the PjBL model increases student creativity, as seen in increased active involvement, ability to collaborate, and development of innovative ideas. In the first cycle, although there was an increase in participation, students still depended on teacher guidance in solving problems. However, in the second cycle, students showed significant improvements in innovation and working independently. The main supporting factors in implementing PjBL are teacher readiness, availability of relevant learning media, and school environment support. Obstacles faced include limited time and students' difficulties in working independently. This research suggests the need to improve teachers' skills in designing projects as well as more efficient time management to overcome these obstacles. Overall, PjBL has proven to be effective in increasing student creativity.